1998
DOI: 10.2307/1543095
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Controlling Stiffness of Connective Tissue in Sea Cucumbers

Abstract: We present the first evidence of a system of four bioactive peptides that affect the stiffness of sea cucumber dermis. The body wall dermis of sea cucumbers consists of catch connective tissue that is characterized by quick and drastic stiffness changes under nervous control. The peptides were isolated from the body wall, their amino acid sequences determined, and identical peptides synthesized. Two peptides, which we named holokinins, are homologous with bradykinin. We tested the effect of the peptides on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 17 publications
0
53
1
Order By: Relevance
“…GABA inhibited the AChinduced contraction in Sclerodactyla briareus , whereas in Actinopyga it had excitatory effects (Devlin, 2001). Muneoka and coworkers (Iwakoshi et al ., 1995;Birenheide et al ., 1998;Ohtani et al ., 1999) isolated 25 peptides from the present sea cucumber. Some of them may well inhibit AChinduced contraction, because about half of the peptides isolated showed inhibitory effects on the twitch contraction of LMBW invoked by electrical stimulation, and because stichopin, one of the 25 peptides, inhibits action of ACh in the body-wall catch connective tissue of the present sea cucumber (Birenheide et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA inhibited the AChinduced contraction in Sclerodactyla briareus , whereas in Actinopyga it had excitatory effects (Devlin, 2001). Muneoka and coworkers (Iwakoshi et al ., 1995;Birenheide et al ., 1998;Ohtani et al ., 1999) isolated 25 peptides from the present sea cucumber. Some of them may well inhibit AChinduced contraction, because about half of the peptides isolated showed inhibitory effects on the twitch contraction of LMBW invoked by electrical stimulation, and because stichopin, one of the 25 peptides, inhibits action of ACh in the body-wall catch connective tissue of the present sea cucumber (Birenheide et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several types of neuropeptides have been found in the nervous system of echinoderms (Thorndyke and Candia Carnevali, 2001). In sea cucumbers, it is suggested that some peptides work as neurotransmitters controlling muscles and catch connective tissues (Díaz-Miranda et al ., 1995;Birenheide et al ., 1998;Inoue et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that Ca 2+ depletion was not the essential condition for producing the soft state. The isolated dermis in nASW softened in response to various stimuli such as acetylcholine, holokinin, an endogenous peptide of sea cucumbers, and very strong mechanical stimulation (Motokawa, 1987;Motokawa, 1988;Birenheide et al, 1998), and thus the dermis could take the soft state with the presence of normal Ca 2+ concentration in bathing media. The exceptional case in nASW of the present study did show that tensilin could exert effects, although not strong, under the normal ionic condition with Ca 2+ .…”
Section: H-tensilin Stiffened the Dermis In The Soft Statementioning
confidence: 99%
“…The three mechanical states differ not only in stiffness but also in various other mechanical parameters such as strain dependence and energy dissipation, and thus the standard state is not simply an intermediate state between the two extremes of soft and stiff states. These states could be produced in isolated dermis by various stimuli and peptides isolated from sea cucumbers (Birenheide et al, 1998). They are also produced by immersion of the isolated dermis in the following media: the standard state in natural seawater or artificial seawater with normal composition (nASW); the soft state in calcium-free artificial seawater (CaFASW); the stiff state in artificial seawater with elevated potassium concentration (KASW) (Motokawa and Tsuchi, 2003).…”
Section: Introductionmentioning
confidence: 99%